Update on therapy for superficial mycoses: review article part I - Maria Fernanda Reis Gavazzoni Dias; Maria Victoria Pinto Quaresma-Santos; Fred Bernardes-Filho; Adriana Gutstein da Fonseca Amorim; Regina Casz Schechtman; David Rubem Azulay (Sociedade Brasileira de Dermatologia, 2013)
Superficial fungal infections of the hair, skin and nails are a major cause of morbidity in the world. Choosing the right treatment is not always simple because of the possibility of drug interactions and side effects. The first part of the article discusses the main treatments for superficial mycoses - keratophytoses, dermatophytosis, candidiasis, with a practical approach to the most commonly-used topical and systemic drugs , referring also to their dosage and duration of use. Promising new, antifungal therapeutic alternatives are also highlighted, as well as available options on the Brazilian and world markets.